Helicobacter pylori CagA seropositivity in adult Bangladeshi patients with peptic ulcer and erosion - Rahman, Fahmida; Shadia, Khandaker; Khatun, Salma; Mahmud, Mafruha; Dutta, Indrajit Kumar; Haq, Jalaluddin Ashraful (IMC Journal of Medical Science, 2020)
Background: CagA IgG antibody in sera might indicate presence of virulent Helicobacter pylori in patients with peptic ulcer disease. Present study was performed to find out the prevalence of CagA IgG antibody in patients with peptic ulcer/erosion. Methods: Any case that had peptic ulcer/erosion, plus positive for rapid urease test (RUT) or H. pylori stool antigen (HpSAg) or serum anti-H. pylori IgG/IgA were included in the study and named as H. pylori positive case. H. pylori positive cases were tested for CagA IgG antibody. Anti-H. pylori IgG, IgA and CagA IgG antibodies were determined by enzyme-linked immunosorbent assay (ELISA) and stool antigen by rapid immunochromatographic test (ICT). Urease production in biopsy sample was detected by RUT. Results: Total 86 H. pylori positive patients were included in the study. Out of 86 patients, CagA IgG was positive in 34 (39.5%; 95% CI: 0.30,0.50) cases. CagA seropositivity rate in ulcer and erosion cases were 58.8% (95% CI: 0.36,0.78) and 34.8% (95% CI: 0.25,0.47) respectively. H. pylori stool antigen and IgA antibodies were positive in all (100%) CagA antibody positive ulcer cases while the rates were significantly less among the CagA antibody negative cases (42.8% and 28.6%; p<0.05). However, in CagA antibody positive erosion cases, the rates were not significantly different from CagA antibody negative cases. Conclusion: The study has demonstrated that the CagA positive strain is less prevalent in erosion than ulcer cases. Ibrahim Med. Coll. J. 2020; 14(1): 36-40